After Effects of Radiation on the Caries Status of Head and Neck Cancer Patients − A Six-Month Clinical Trial - Upasana Reddy; Mithra N. Hegde; Aditya Shetty; Mallikarjuna Rao Koduru; Neevan Dsouza (Journal of Pharmacy and Bioallied Sciences)
Background: Head and neck cancer patients undergoing radiation therapy (RT) are at an increased risk of dental caries due to radiation-induced damage to salivary glands. This study aimed to compare the effectiveness of three interventions—virgin coconut oil (VCO), casein phosphopeptide-amorphous calcium phosphate tooth mousse (TM), and amine fluoride mouthwash (MW)—in preventing caries among head and neck cancer patients’ post-radiation therapy. Methods: A total of 102 head and neck cancer patients undergoing RT were enrolled. The participants were randomized to use one of three interventions: VCO, TM, or MW. Caries progression was assessed using the decayed-missing-filled-teeth (DMFT) index at baseline and after 6 months of RT. Differences in DMFT scores between the groups were analysed using statistical tests. Results: At the 6-month follow-up, significant differences in DMFT scores were observed between the VCO and MW groups (P = 0.012) and between the MW and TM groups (P = 0.001). The TM group showed a significant reduction in caries progression compared to both the VCO and MW groups (P = 0.001). Conclusions: Casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) tooth mousse was found to be the most effective in preventing new caries and slowing the progression of existing carious lesions in head and neck cancer patients undergoing radiation therapy.